2019
DOI: 10.1039/c9dt00690g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, physico-chemical characterization and structure of the elusive hydroxylammonium lead iodide perovskite NH3OHPbI3

Abstract: The elusive hydroxylammonium lead iodide NH3OHPbI3 has been successfully synthesized and characterized for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…In contrast, a recent study indicates that FM was not successfully embedded in the perovskite structure, but rather it was included as an additive [36], despite the similarity with the FA cation. The pure usage of HA cations yields structures with face-sharing octahedra that differ from the standard, corner-sharing perovskites [37]. This is despite the fact that the Goldsmith factor would indicate a typical 3D structure is possible and the anomaly was explained by the formation of hydrogen bonds.…”
Section: Mixed-cation Mixed-halide Perovskitesmentioning
confidence: 93%
“…In contrast, a recent study indicates that FM was not successfully embedded in the perovskite structure, but rather it was included as an additive [36], despite the similarity with the FA cation. The pure usage of HA cations yields structures with face-sharing octahedra that differ from the standard, corner-sharing perovskites [37]. This is despite the fact that the Goldsmith factor would indicate a typical 3D structure is possible and the anomaly was explained by the formation of hydrogen bonds.…”
Section: Mixed-cation Mixed-halide Perovskitesmentioning
confidence: 93%
“…Thus, the 3D structure is predicted to be stable when the tolerance factor is between 0.8 and 1.0, and this condition is satisfied only for cesium, methylammonium (MA + ), hydroxylammonium (NH 3 OH + ), hydrazinium (NH 2 NH 3 + ), azetidinium ((CH 2 ) 3 NH 2 + ), formamidinium (FA + ), and imidazolium (C 3 N 2 H 5 + ) cations . Experimental studies show that the real situation is even worse because 3D perovskites containing corner-sharing PbX 6 octahedra thus far comprised only MA + , FA + , or Cs + as cations, while for the remaining small organic cations, a nonperovskite or layered perovskite structure were formed. It is worth adding that, most recently, a new 3D lead halide perovskite-related ferroelectric [2-trimethylammonioethylammonium]­Pb 2 Cl 6 was reported that, however, has a different lead chloride framework of both corner- and edge-sharing PbCl 6 octahedra …”
Section: Introductionmentioning
confidence: 99%
“…However, interestingly, the successful synthesis of the corresponding perovskite has not been reported for some amines with a similar radius as MA + , such as hydrazinium and fluoroammonium ions [30] . Although NH 3 OHPbI 3 with an A‐site cation of 216 pm can be synthesized, it is unsuitable for photovoltaic applications because of its low melting and decomposition temperatures (80 °C and 103 °C, respectively) [31] . This indicates that, in addition to the ion size effect, coordination effects, including hydrogen bonds, dipole moments, etc., may also play important roles in the structural stability of FAPbI 3 [32] …”
Section: Functional Construction Of Different Structural Aminesmentioning
confidence: 99%